Spelet och maskerna i August Strindbergs En dåres försvarstal - Bukowski, Piotr (Folia Scandinavica Posnaniensia, 2007)
The aim of the article is to describe and analyse the principal types and strategies of role-playing in August Strindberg's autobiographical novel A Madman's Defence (1887-88). The starting point of this study is the assumption that the main characters in the novel - Axel (Strindberg's alter ego) and Maria - consciously play with masks in order to delude and manipulate people. The following analysis reveals the philosophical premises that determine Axers and Maria's role-playing.